Anti-epidermal growth factor receptor therapy in combination with chemoradiotherapy for the treatment of locally advanced anal canal carcinoma: Results of a phase I dose-escalation study with panitumumab (FFCD 0904). (November 2019) - Vendrely, Véronique; Lemanski, Claire; Gnep, Khemara; Barbier, Emilie; Hajbi, Farid El; Lledo, Gerard; Dahan, Laëtitia; Terrebonne, Eric; Manfredi, Sylvain; Mirabel, Xavier; Mammar, Vincent; Cowen, Didier; et al.
Highlights: The maximum tolerated dose was 5FU 400 mg/m 2 /day, Pmab 3 mg/kg and MMC 10 mg/m 2 . Dose limiting toxicities occurred in 5 of 9 treated patients with panitumumab. Haematologic, dermatitis and anaemia were most common grade 3–4 toxicities. No death occurred during the treatment period. Relevant effects on tumour response were observed. Abstract: Background and purpose: Standard treatment of epidermoid anal cancer is 5-fluorouracil (5FU) and mitomycin C (MMC) based chemoradiotherapy (CRT). This phase I study aims to evaluate the addition of panitumumab (Pmab) to CRT and to determine the maximum tolerated dose (MTD) of Pmab and 5-FU in combination with CRT. Materials and methods: Immunocompetent patients with locally advanced tumour without metastases (Stage T2, T3 or T4, whatever N stage; Stage N1–N3 whatever T stage) followed two RT periods (45 Gy in 5 weeks and 20 Gy in 2 weeks, separated by a 2-week break) with concomitant CT sessions of 5FU/MMC at RT weeks 1, 5 and 8. Pmab was administered on RT weeks 1, 3, 5, 8 and 10 according to a predefined dose escalation schedule. Results: Ten patients were enroled. One was excluded due to unmet dose constraints respect. Three patients received dose level (DL) 0 (Pmab 3 mg/kg + 5FU 600 mg/m 2 /day) and six received DL-1 (Pmab 3 mg/kg + 5FU 400 mg/m 2 /day). Dose-limiting toxicities occurred in all patients at DL 0 and 2 at DL-1. Most common grade 3–4 toxicities observed at DL 0 were haematologic (100%), dermatitis (67%), and anaemia (67%). No death occurred. Four months after ending CRT, five and two patients had a local complete response and a partial response, respectively. One patient had a colostomy with abdomino-perineal amputation due to a tumour recurrence. Conclusions: The MTD is 5FU at 400 mg/m 2 /day, MMC at 10 mg/m 2 and Pmab at 3 mg/kg. The effect of the MTD on tumour response is evaluated in the phase 2 study.